Pemetaan Strategi Komunikasi Brand Produk Hair Tonic di Indonesia - Arly, Rachel; Muljosumarto, Cindy; Sylvia, Merry (Universitas Komputer Indonesia, 2025)
Hair tonic is one of the products developed to help with hair care. Unfortunately, the marketing of this product is mixed. The brand communication strategy between categories is difficult to distinguish, making the information, product content, uniqueness, and targets of the brand mixed and less recognized by consumers. Therefore, an analysis of consumer insight, character, preferences, and communication was carried out, along with mapping of brand communication strategies by using a qualitative descriptive comparative method. Interview and observation were conducted to gather data to prove product categories based on content, then compared with consumer communication as a benchmark for brand communication strategy success. This study aims to provide assistance in the form of a guideline for other brands that have similar categories and objectives in implementing the right brand communication strategy in running the brand, educating consumers regarding product functions and content, and solving consumer problems. In the end, this study proves that the brand category is successful and in accordance with the brand communication strategy.